Internal Conflict of the National Awakening Party in Karawang Regency: Sources and Impact of Conflict in the 2009 Election - Bambang Bambang (The International Journal of Politics and Sociology Research, 2021)
The National Awakening Party is one of the Islamic political parties in Indonesia which was declared at the Wahid Hasyim Islamic Boarding School in Ciganjur, South Jakarta, was attended by Nahdlatul Ulama kiai, including KH. Munasir Ali, KH. Ilyas Ruchiyat, KH. Abdurrahman Wahid, KH. Mostofa Bisri, and KH. Muhith Muzadi. As a new party, PKB participated in the 1999 general election which got third place after PDIP and Golkar. The laying of the foundation stone for the PKB journey is still rising in Indonesian politics. However, PKB as an Islamic political party experienced various trials and obstacles that began with the conflict spearheaded by Gus Dur and Matori, in his case Matori's presence at the MPR session in the context of Gus Dur's removal from the presidency. So at the same time Gus Dur fired Matori who was considered to have violated the party's rules to participate in the MPR session, the conflict was getting wider so that it reached the court. In this case, PKB was divided into two camps, namely the Batutulis camp led by Matori and the Kuningan PKB led by Gus Dur. However, in the decision of the trial court, Gus Dur's camp won the case. Until he participated in the 2004 general election, he did not experience any problems. Furthermore, in the United Indonesia Cabinet (KIB) under the leadership of Susilo Bambang Yudoyono and Jusuf Kalla, they chose Alwi and Saefullah Yusuf as ministers, and this resulted in both being fired from the party management because they were deemed to have violated party rules. So that this case also went to court because Alwi and Saefullah did not accept Gus Dur's decision. The conflicts that occurred were carried out by several actors, namely Gus Dur, Matori and Alwi, from the first, second, and third conflicts, it did not affect the DPC PKB Karawang. Therefore, here the author will explain and describe the conflicts that occur at the district or city level, namely in the district. Karawang. Because, In fact, conflicts that occur at the central level have an impact on the branch or city level. The extent to which the impact and influence of the conflict on society (Nahdliyin) and elections. This is because, in fact, conflict greatly affects both the central and branch levels.